A selective review of recent quantitative empirical research in Marxist political economy - Basu Deepankar (University of Massachusetts, Department of Economics, 2015)
This paper surveys some of the quantitative empirical research in two areas of Marxist political economy: (a) Marxist national accounts, and (b) Marxist responses to the Sraffa-based critique of the 1970s. With respect to the first area, this paper explains the basic methodology underlying the construction of Marxist national accounts from traditional input-output data. With respect to the second area, it offers a short review of the theoretical literature surrounding the Sraffa-based critique of the 1970s, and subsequently discusses three Marxist responses in detail: the standard interpretation, the probabilistic interpretation and the new interpretation. It explains the basic theoretical positions of these three approaches and reviews the quantitative empirical work conducted within each.
Keywords: B51; C1; 330; Marxist political economy; national accounts; value controversy